Improving net enAergy gain in fermentative biohydrogen production from glucose - Ketheesan, B.; Nirmalakhandan, N. (Elsevier, 2011)
Our previous studies had demonstrated enhanced fermentative hydrogen production from sucrose in batch reactors with dairy manure as a supplement providing nutrients, buffering, and hydrogen-producing organisms. In this study, manure leachate is evaluated as a supplement in glucose fermentation in batch and continuous flow reactors at 25 C without any nutrient supplements, initial pH adjustments, buffering, or stirring. Hydrogen yields found in this study are comparable to or better than those reported at higher temperatures. When the heat energy expended to maintain the test temperatures is considered, positive net energy gain of w10 kJ/L of reactor volume was achieved while most literature reports translated to negative net energy gain. Anaerobic digestion (AD) and microbial fuel cells (MFC) were evaluated as follow-up processes to extract additional energy from the end products of dark fermentation (DF). This evaluation showed that DF followed by MFCs to produce electricity to be a more energy-efficient approach.
Keywords: Fermentative hydrogen production; Manure leachate; Net energy gain; Anaerobic digestion